Estimation method of support reaction on face sheet of sandwich panel by inverse analysis of deformed shape data - Yoshinao KISHIMOTO (The Japan Society of Mechanical Engineers, 2016)
When local compressive load is vertically applied on the face sheet of the sandwich panel, the face sheet will be deflected and the core layer will be crushed at relatively low load. In order to evaluate the mechanical property of the sandwich panel subjected to the local compression, it is important to estimate the reaction on the face sheet supported by the core layer. However it is difficult to directly measure the support reaction because the core layer has been crushed. This paper describes a novel method to estimate the support reaction on the face sheet of the sandwich panel by inverse analysis of the deformed shape data of the face sheet. In this method, the finite element method based on strain increment theory is applied to the face sheet using the measured deflection of the face sheet as the boundary condition. Then it estimates the nodal load of the finite element model of the face sheet that is equivalent to the support reaction by the Tikhonov regularization. In order to demonstrate the validity of the proposed method, numerical simulations have been performed. In the numerical simulations, the several support conditions of the face sheet were given in advance. Then the direct analysis was applied to obtain the correct support reaction and the deformed shape of the face sheet in each condition. The inverse analysis was applied on the simulation data of the deformed shape to estimate the support reaction. The results show that the support reaction estimated by the proposed method has good agreement with the correct value. Moreover, it is concluded that the proposed method requires the location of the support point as a priori information.